Professional Registration of Probation Practitioners in a Devolved Welsh Probation Service - Deering, John (Probation journal, 2025)
In this paper, we consider the newly implemented Probation Professional Register Policy Framework in the context of the intent of the Welsh Government (WG) to work towards the devolution of justice, including probation. Thus, we reflect on devolution and its potential implications, the specific forms of partnership working and development in Wales, probation organisational culture, and questions of probation's legitimacy. We suggest that to make the most of the professional register's potential for professionalisation of probation practice, it needs to be embedded in an organisational structure and culture that fully owns and promotes the ethics and values of partnership working, taking a rights-based approach in the support for those who cause harm to victims and communities, and evidence-based practice.